The effect of johari window training on self-esteem of the adolescents at aisyiyah orphanage in sidoarjo - Putri Nandiita; Effy Wardati Maryam (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study is aimed to increase self-esteem of the adolescents at Aisyiyah orphanage in Sidoarjo by using the Johari Window self-awareness training. Quantitative experimental approach was implemented in this study with paired samples T-test for data analysis. Data were collected from three meetings by comparing the pretest and posttest results of self-esteem scale questionnaire. An improvement in self-esteem was seen on some aspects, which were (1) self-contentment, (2) awareness on one’s strength, (3) feeling of proud and worth, and (4) positive attitude and thinking. This improvement was shown by significant change on adolescents’ self-esteem after they participated in the Johari Window training with a mean difference of 2.200, t-score =-4.147 and p = 0.001 <0.05. Besides, the Cohen's d value, which was 0.757, showed a large effect. It is concluded that the Johari Window training method can increase the adolescents’ understanding of self-esteem and motivation in spending their days in orphanage, school, and home